2017
DOI: 10.1039/c7sc01615h
|View full text |Cite
|
Sign up to set email alerts
|

A nickel nanocatalyst within a h-BN shell for enhanced hydrogen oxidation reactions

Abstract: The confinement effect of h-BN shells helps to maintain active metallic Ni cores and strengthen the HOR processes occurring at h-BN/Ni interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 48 publications
3
92
0
Order By: Relevance
“…Copyright 2017, Royal Society of Chemistry. c) Reproduced with permission . Copyright 2017, Royal Society of Chemistry.…”
Section: Catalysis With 2d Cover‐confined Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2017, Royal Society of Chemistry. c) Reproduced with permission . Copyright 2017, Royal Society of Chemistry.…”
Section: Catalysis With 2d Cover‐confined Metalsmentioning
confidence: 99%
“…The confined nanospace between 2D cover and inner metal offers an ideal micro‐environment for exploring the confinement catalysis experimentally and theoretically. For instance, Gao et al presented a simple and practical synthesis way to encapsulate Ni nanoparticles within few‐layer h‐BN cover . This unique catalyst exhibited an improved catalytic performance in the hydrogen oxidation reaction process compared with bulk metal nanoparticles (Figure c).…”
Section: Catalysis With 2d Cover‐confined Metalsmentioning
confidence: 99%
“…This is attributed to the fact that the hexagonal BN lacks the delocalized p electrons, and the electron penetration of Ni to the BN layers is limited. [33,34] The study of the electron-shift-induced catalysis over Ni@C for promoting ethanol formation is in progress.…”
Section: Catalytic Performancementioning
confidence: 99%
“…Whereas PGM‐free oxygen reduction reaction (ORR) catalysts exhibit comparable activity to PGM catalysts, PGM‐free hydrogen oxidation reaction (HOR) catalysts are much inferior . Despite several decades of research, only nickel and its metallic alloys have been shown to be active PGM‐free HOR catalysts ,. Recently Yan and co‐workers significantly improved the activity of Ni nanoparticles in HOR using a nitrogen‐doped carbon nanotube support .…”
Section: Figurementioning
confidence: 99%